Effects of butyric acid glycerol ester supplementation on intestinal nutrient transporter and immune-related genes in broiler chickens challenged with Eimeria maxima - Kpodo, Kouassi R.; Miska, Katarzyna B.; Schreier, Lori L.; Milliken, Daniel J.; Proszkowiec-Weglarz, Monika (Frontiers in Veterinary Science, 2025)
IntroductionCoccidiosis negatively affects intestinal health and digestive functions; however, whether butyric acid glycerol ester (BE) can mitigate these negative effects in broiler chickens is unknown. The study objective was to determine the effects of BE on nutrient transporter and intestinal immune genes in chickens infected with Eimeria maxima (EM).MethodsRoss male 708 chicks were fed diets supplemented with 0 (control, C) or 0.25% of BE. On day 21, half the chickens from each feeding group were infected with 0 or 103 EM sporulated oocysts creating four treatment groups (C, +EM, +BE, and BE + EM; n = 6/treatment group). Jejunal and ileal tissues were collected at days 7 and 10 post-infection (PI).ResultsEM infection reduced (P ≤ 0.02) nutrient transporter genes EAAT3, PEPT2, B°AT, GLUT2, GLUT5, and SGLT1 at days 7 PI in the jejunum and ileum and EAAT3, PEPT1, PEPT2, and B°AT at day 10 PI in the jejunum. The supplementation of BE increased CAT1 in the jejunum and PEPT1, GLUT2, and GLUT5 (P ≤ 0.04) in the ileum at day 10 PI. A BE x EM interaction was observed (P ≤ 0.02) where GLUT1 and GLUT2 were increased in the jejunum of +BE compared to C chickens at day 10 PI. Among the immune-related genes, EM reduced (P ≤ 0.0001) IgA in the jejunum but increased (P = 0.004) TGF-β4 in the jejunum and ileum at day 7 PI. The expression of pIgR was reduced, while TLR2 and TLR4 were increased in +EM compared to C chickens at day 7 PI. In addition, IgA was increased (P = 0.01) in the ileum of +BE compared to C chickens at day 10 PI.ConclusionThe results of the study confirmed that Eimeria maxima reduced nutrient transporters and immune-related genes in the jejunum and ileum of chickens. However, although BE increased the expression of some genes in non-challenged chickens, its supplementation did not prevent the reduction in the expression of selected genes caused by EM infection.